Macro-Micro Feedback Links of Water Management in South Africa : CGE Analyses of Selected Policy Regimes - Hassan, R.; Thurlow, J.; Roe, T.; Diao, X.; Chumi., S.; Tsur, Y. (World Bank, Washington, DC, 2012)
The pressure on an already stressed water situation in South Africa is predicted to increase significantly under climate change, plans for large industrial expansion, observed rapid urbanization, and government programs to provide access to water to millions of previously excluded people. The present study employed a general equilibrium approach to examine the economy-wide impacts of selected macro and water related policy reforms on water use and allocation, rural livelihoods, and the economy at large. The analyses reveal that implicit crop-level water quotas reduce the amount of irrigated land allocated to higher-value horticultural crops and create higher shadow rents for production of lower-value, water-intensive field crops, such as sugarcane and fodder. Accordingly, liberalizing local water allocation in irrigation agriculture is found to work in favor of higher-value crops, and expand agricultural production and exports and farm employment. Allowing for water trade between irrigation and non-agricultural uses fueled by higher competition for water from industrial expansion and urbanization leads to greater water shadow prices for irrigation water with reduced income and employment benefits to rural households and higher gains for non-agricultural households. The analyses show difficult tradeoffs between general economic gains and higher water prices, making irrigation subsidies difficult to justify.